Sistem Informasi Pelanggaran Siswa Berbasis Web Pada SMP Negeri 42 Padang - Ichsan Syah Putra Ihsan; Danyl Mallisza (JENTIK, 2025)
Student discipline and order are highly expected by the school. To maintain this, SMPN 42 Padang implements a point system for students who violate the rules of discipline. However, this system is still less than optimal because the process of recording violations is still done manually using books. Therefore, it is necessary to develop a web-based student violation information system. This research is included in the type of development research (Research and Development) with a Software Development Life Cycle (SDLC) approach. Data collection methods are carried out through observation, interviews, and literature studies. The result of this research is a web-based application for managing student violation data at SMPN 42 Padang which is expected to assist the school in carrying out the violation administration process more quickly, effectively, and efficiently.